The Regulatory Concept of Cyber Notary in Indonesia: Konsep Pengaturan Cyber Notary di Indonesia - Pangesti, Shinta; Darmawan, Grace I; Limantara, Cynthia P. (Universitas Muhammadiyah Sidoarjo, 2020)
Notary has the authority to certify the electronic transaction (cyber notary) according to the Elucidation of Article 15 paragraph (3) of Law Number 2 of 2014 (Law 2/2014). Thus, the authority has been the milestone for the concept of cyber notary in Indonesia. Although the enactment of Law 2/2014 presented a new concept in Notary in Indonesia, but it does not give a wide chance to the application of cyber notary itself. One of the roots that causes the obstacles are the absence of definite law in regulating cyber notary. Law 2/2014 mentioned cyber notary but did not give a normative definition on it. Therefore, the concept of cyber notary is limited to conduct the certification of electronic transaction. Several challenges on performing the authorities and obligations of notary could be found in the context of the implementation of cyber notary, as follows: 1) Notary is bounded to the form and procedure in drawing up authentic deeds set by Article 38 Law 2/2014; 2 ) The appearers shall be known to Notary or introduced to him/her; 3 ) Reading and signing of deeds have to done in specific procedure; and 4) Drawing up deeds in the form of Minutes of Deed and keep the same as a part of Notarial Protocols. This article was classified as legal normative research and meant to analyze the concept of regulation on cyber notary in Indonesia by using statute and conceptual approach.